Prediksi Kebangrutan Perusahaan Energy dan Basic Materials dengan Notasi Khusus Menggunakan Model Zmijewski dan Grover - Rokhmah, Fani Hafida; Suhadi, Suhadi (Institut Agama Islam Negeri Kudus, 2025)
AbstractThis research is motivated by the increasing risk of financial distress and bankruptcy in energy and basic materials sector companies in Indonesia, which is reflected in the large number of companies with the special notation